AN ANALYSIS OF INTRAPERSONAL INTELLIGENCE AS THE SOLUTION FOR BEGINNER WRITER - Imran Trista Udin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The objectives of this research were to find out whether the use of intrapersonal intelligence improves the students’ writing skills This research employed a Quasi-Experimental design. The sample consisted of 68 students in the third semester of business administration, academic year 2023/ 2024 Politeknik LP3I Makassar. The data were collected through the instrument: writing test for the student’s writing skills. Data on the students’ writing skills were analyzed using descriptive and inferential statistics. The results of the research were: that the use of intrapersonal intelligence in teaching writing improved the students’ writing skills. Based on the result of data analysis as summarized on the pretest of the experimental and control groups, the researcher found that the Probability value (0.86) is higher than the level of significance at t-table (0.05) and the degree of freedom 58. It means that H0 was accepted and H1 was rejected. In other words, there was no significant difference between the students’ writing skills in both groups, the experimental and control groups before the treatment. It is supported by Gay (2006:124) states that when variables have equal intervals, it is assumed that the difference between close scores is essentially the same. The data on the posttest of the control and experimental group showed that the probability value was smaller than α (0.00<0.05). It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It means that Intrapersonal intelligence significantly increased the students’ writing skills. It can be concluded that the use of intrapersonal intelligence is effective to be implemented in improving the students’ writing skills.